Metodologi Penafsiran Al-Qur'an - Misbahus Surur (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2019)
When we hear the word "tafsir" we will definitely conclude about the explanation of the Qur'an verse by verse, letter by letter until the last letter of the Qur'an. Even though the interpretation is not like that, the verse by verse explanation is only one of the many methods of interpreting the Qur'an. emergence and development and the sources used in interpretation.